2018
DOI: 10.1016/j.chemphyslip.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Temperature triggering of kinetically trapped self-assemblies in citrem-phospholipid nanoparticles

Abstract: Temperature triggering of kinetically trapped self-assemblies in citrem-phospholipid nanoparticles. Physics and Chemistry of Liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
2
12
1
Order By: Relevance
“…Thus, the replacement of sodium caseinate by citrem did not induce any significant change in the d -spacing of the L α phase. These results indicate that there is no significant incorporation of sodium caseinate or citrem into AO during the emulsion preparation and digestion, and are in contrast with our previous findings on the significant effect of this emulsifier (citrem) on the structural features of lamellar and non-lamellar liquid crystalline nanoparticles based on soybean phospholipid, ω-3 PUFA monoglycerides, or monoolein (Hedegaard et al, 2013; Azmi et al, 2015, 2016; Wibroe et al, 2015; Yaghmur et al, 2017; Prajapati et al, 2018; Shao et al, 2018). The time evolution of the first order reflection of the L α phase and the single exponential function used to fit the SAXS data (full blue line) are presented in Figure 5D.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, the replacement of sodium caseinate by citrem did not induce any significant change in the d -spacing of the L α phase. These results indicate that there is no significant incorporation of sodium caseinate or citrem into AO during the emulsion preparation and digestion, and are in contrast with our previous findings on the significant effect of this emulsifier (citrem) on the structural features of lamellar and non-lamellar liquid crystalline nanoparticles based on soybean phospholipid, ω-3 PUFA monoglycerides, or monoolein (Hedegaard et al, 2013; Azmi et al, 2015, 2016; Wibroe et al, 2015; Yaghmur et al, 2017; Prajapati et al, 2018; Shao et al, 2018). The time evolution of the first order reflection of the L α phase and the single exponential function used to fit the SAXS data (full blue line) are presented in Figure 5D.…”
Section: Resultscontrasting
confidence: 99%
“…In literature, it was reported that a good colloidal stability for ionic aqueous dispersions including emulsions can be achieved in the presence of single charged emulsifiers such as citrem on dispersing droplets with zeta potential values around ±30 mV in excess water (Honary and Zahir, 2013). In addition to its use as stabilizer with an anti-oxidative property for various food emulsions (Gudipati et al, 2010; Berton et al, 2011), citrem is attractive for use as a safe emulsifier for stabilizing lamellar and non-lamellar liquid crystalline nanoparticles owing to its hemocompatiblity and poor activation of the complement system (Nilsson et al, 2012; Hedegaard et al, 2013; Wibroe et al, 2015; Prajapati et al, 2018). In our study, the three investigated samples were visually inspected and found to be colloidally stable at room temperature for at least 3 months after preparation, see images in Figure 2B.…”
Section: Resultsmentioning
confidence: 99%
“…In absence of TQ (samples A1 and A2), the mean (±SD) nanoparticle sizes (diameters) of the two produced nanodispersions at TFR of 100 and 50 µL/min were ranging from 115.5 ± 42 to 119.7 ± 42 (Table 1). These mean sizes and modes were comparable with those previously reported for ethanol-free citrem/SPC nanodispersions prepared at same citrem/SPC lipid composition by using two different batch methods: a low-energy emulsification method (vortexing for few minutes) and a high-energy emulsification method based on ultrasonication [30,33]. In addition to a possible effect of ethanol on size characteristics, it is important to take into account that citrem is a commercial lipid and a batch-to-batch variability in its composition could contribute to slight alterations in the size characteristics and structural features of this family of citrem/SPC nanoparticles, as discussed in a recent report [33].…”
Section: Size Characteristics Of Tq-free and Tq-loaded Citrem/spc Nano Self-assembliessupporting
confidence: 89%
“…The effects of TQ loading and ethanol concentrations on the structural features of citrem/SPC nanoparticles were investigated by synchrotron SAXS at 25 • C. Here, we considered the reported sensitivity of citrem/SPC nano-self-assemblies to variations in their lipid composition and loaded drug concentration [28,30,33]. At a constant citrem/SPC of 2:3, the investigated TQ-free and TQ-loaded nanodispersions were prepared by employing the low energy batch emulsification method, and contained lipid (citrem and SPC) and EtOH concentrations of 8.0 and 1.09 wt%, respectively.…”
Section: Effects Of Loading Drug and Etoh Concentration On Citrem/spc Nano Self-assemblies Produced By The Batch Emulsification Methodsmentioning
confidence: 99%
See 1 more Smart Citation